Tarik Ulur Hukum Adat dan Hukum Islam dalam Hukum Positif di Indonesia - El Falahy, Lutfi (Institut Agama Islam Negeri Curup, 2020)
Indonesia has written law in the form of positive law and law that lives in recognized societies and then becomes customary law, but recognition of customary law applies only to groups that recognize its existence, of course this is contrary to positive law that applies universally. Here the author tries to examine how the role of customary law in the formation of positive law and what its effects. The method used in this paper is a qualitative method and the approach uses library research. As a rule of law aimed at creating harmony and balance in society, the existence of customary law in a rule of law is absolutely necessary, because the rule of law as a feature of the rule of law is not a final word, but as a way to create justice in society.